Colour in Iberian Iron Age architectural sculpture: the case of Cerro de la Merced - Quesada Sanz, Fernando (2025)
Recently, analytical research has confirmed the use of pigments in Iberian Iron Age freestanding sculpture. However, hard evidence of polychromy on the many preserved remains of architectural sculpture is still scarce. We focus on the case of a large block decorated with reliefs, probably dated to the end of the 5th or the beginning of the 4th century BCE, recently found at Cerro de la Merced (Cabra, Córdoba). Employing optical and electron microscopy analyses, FTIR spectroscopy, and GC-MS, it has been possible to confirm the existence of traces of red and white colour covering the entire surface, analyse the composition of the pigments employed, and to reconstruct the colour patterns of the different elements of the relief. Our aim is to deepen our understanding of the use of colour in Iberian architecture and to shed light on the colours employed, the techniques used to apply them and their arrangement patterns.